2006
DOI: 10.1063/1.2364839
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency light-emitting column-crystallized InGaN∕GaN quantum-well flower structure on micropillared Si substrate

Abstract: Column-crystallized InGaN∕GaN quantum-well flower structure was deposited on pillared Si (111) substrate. Dotted GaN nuclei grew along the direction of the coming Ga and N atoms, forming arrays of InGaN∕GaN quantum-well flower structure. Raman spectra measurement demonstrated that these crystals were fully relaxed. Photoluminescence measurement showed a room temperature peak position of 556nm and two peak positions of 400 and 549nm at low temperature. Hg lamp excited photoluminescence demonstrated a clear fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Although the crystal was not continuous, the nano-column GaN crystals grown by MBE were shown to have a good crystalline quality and an excellent optical property (Kikuchi et al 2004;Hu et al 2006). In the recent researches, the high efficient LED and laser oscillation were reported.…”
Section: Gan Crystalline Growth On Si Wafermentioning
confidence: 98%
“…Although the crystal was not continuous, the nano-column GaN crystals grown by MBE were shown to have a good crystalline quality and an excellent optical property (Kikuchi et al 2004;Hu et al 2006). In the recent researches, the high efficient LED and laser oscillation were reported.…”
Section: Gan Crystalline Growth On Si Wafermentioning
confidence: 98%
“…We tested several buffer layers for the growth of GaN crystal on Si (111) substrate such as low temperature AlN/GaN layers using MBE. The crystals were likely to become nano-columns of the diameter around 150 nm (Hu et al 2006). Although the nano-column crystals had several unique properties and we successfully fabricated the nanocolumn LED on Si substrate (Ito et al 2010), the special technique was needed for filling the spaces between the nano-columns to fabricate the electrode on p-GaN layer.…”
Section: Gan Crystal Growth On Si Substrate and Led Fabricationmentioning
confidence: 99%
“…A RF nitrogen plasma source and solid Ga and In source were used as the source materials. After several experiments, it was found that nanocolumn QW crystals on Si have better quality and the photoluminescence (PL) is more efficient, compared with the flat QW crystal on Si [4][5][6][7]. In order to decrease the defects, a low-temperature buffer layer (GaN, nitrified Ga dots or InN interlayer) was first deposited on the Si substrate, and then it was followed by the deposition of the high-temperature GaN.…”
Section: Introductionmentioning
confidence: 99%